Enrichment of extracellular vesicles from human synovial fluid using size exclusion chromatography. Issue 1 (26th June 2018) - Foers, Andrew D.; Chatfield, Simon; Dagley, Laura F.; Scicluna, Benjamin J.; Webb, Andrew I.; Cheng, Lesley; Hill, Andrew F.; Wicks, Ian P.; Pang, Ken C.
ABSTRACT: As a complex biological fluid, human synovial fluid (SF) presents challenges for extracellular vesicle (EV) enrichment using standard methods. In this study of human SF, a size exclusion chromatography (SEC)‐based method of EV enrichment is shown to deplete contaminants that remain after standard ultracentrifugation‐based enrichment methods. Specifically, considerable levels of serum albumin, the high‐density lipoprotein marker, apolipoprotein A‐I, fibronectin and other extracellular proteins and debris are present in EVs prepared by differential ultracentrifugation. While the addition of a sucrose density gradient purification step improved purification quality, some contamination remained. In contrast, using a SEC‐based approach, SF EVs were efficiently separated from serum albumin, apolipoprotein A‐I and additional contaminating proteins that co‐purified with high‐speed centrifugation. Finally, using high‐resolution mass spectrometry analysis, we found that residual contaminants which remain after SEC, such as fibronectin and other extracellular proteins, can be successfully depleted by proteinase K. Taken together, our results highlight the limitations of ultracentrifugation‐based methods of EV isolation from complex biological fluids and suggest that SEC can be used to obtain higher purity EV samples. In this way, SEC‐based methods are likely to be useful for identifying EV‐enriched components and improving understanding of EV function in disease.